2021
DOI: 10.3390/cancers13163992
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report on Computed Tomography Radiomics Features as Biomarkers to Immunotherapy Selection in Lung Adenocarcinoma Patients

Abstract: Purpose: To assess the efficacy of radiomics features obtained by computed tomography (CT) examination as biomarkers in order to select patients with lung adenocarcinoma who would benefit from immunotherapy. Methods: Seventy-four patients (median age 63 years, range 42–86 years) with histologically confirmed lung cancer who underwent immunotherapy as first- or second-line therapy and who had baseline CT studies were enrolled in this approved retrospective study. As a control group, we selected 50 patients (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…The "Clinical Evaluation" section collected previous examination results, a genetic panel, results of histopathological exami-nation on biopsy specimen, carbohydrate antigen 19.9 (Ca 19.9) level, carcinoembryonic antigen (CEA) level, blood count, serum creatinine, liver function, and clinical symptoms. These data could create the basis of a large database, allowing not only for the carrying out of epidemiological statistical analysis, but they could be used to build a radiomics model by combining radiological features and clinical data [33][34][35][36][37][38][39]. In this context, the added value of genomic data could be used to develop a model of radiogenomics, which was helpful regarding the highest level of personalized risk stratification and the advanced precision medicine process [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The "Clinical Evaluation" section collected previous examination results, a genetic panel, results of histopathological exami-nation on biopsy specimen, carbohydrate antigen 19.9 (Ca 19.9) level, carcinoembryonic antigen (CEA) level, blood count, serum creatinine, liver function, and clinical symptoms. These data could create the basis of a large database, allowing not only for the carrying out of epidemiological statistical analysis, but they could be used to build a radiomics model by combining radiological features and clinical data [33][34][35][36][37][38][39]. In this context, the added value of genomic data could be used to develop a model of radiogenomics, which was helpful regarding the highest level of personalized risk stratification and the advanced precision medicine process [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…According to Johns Hopkins University, case-fatality rates of COVID-19 patients ranges between 1% and 7% based on days since first confirmed case, testing efficacy, local pandemic response policies, and the population age [45][46][47][48][49]. Multi-organ manifestations of COVID-19 are now well-documented [50][51][52][53][54][55][56][57], but the potential long-term implications of these manifestations remain to be uncovered. Several studies have reported impaired exercise capacity and diffusing capacity for carbon monoxide (DL CO ) in SARS-CoV-1 survivors extending from 6 months to 15 years of follow-up [58][59][60][61][62][63][64], suggesting impairment of the intra-alveolar diffusion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In oncology, the assessment of tissue heterogeneity is of particular interest; genomic analyses have demonstrated that the degree of tumor heterogeneity is a prognostic determinant of survival and an obstacle to cancer control. Studies have demonstrated that radiomics features are strongly correlated with heterogeneity indices at the cellular level [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, that Radiomics could support cancer detection, diagnosis, evaluation of prognosis and response to treatment, so as could supervise disease status [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though individual features may correlate with genomic data, so-called radiogenomics, or clinical outcomes, the impact of radiomics is increased when the data are processed using machine learning techniques. Nowadays, several studies have assessed the role of radiogenomics in hepatocellular carcinoma, but only a few have examined liver metastases [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%